1997
DOI: 10.1086/515554
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence of Oropharyngeal Carriage of Fluconazole‐ResistantCandidain Human Immunodeficiency Virus–Infected Patients

Abstract: To estimate the prevalence of both clinically evident and asymptomatic carriage of fluconazole-resistant Candida, we prospectively surveyed 128 adults infected with human immunodeficiency virus (HIV). The patients had an average CD4 cell count of 206/mm3. Ninety-seven isolates of Candida were obtained from the oropharynx of 82 patients (64%). Of these 82 patients, 76% carried C. albicans alone; 18%, both albicans and non-albicans isolates; and 6%, non-albicans species alone. Oropharyngeal candidiasis was evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 8 publications
2
33
1
1
Order By: Relevance
“…This may be due to the infrequent use of 5-fluorocytosine in dentistry. Varying susceptibility of the tested isolates to the azolegroup antifungal agents is in accordance with recent reports of oral yeast isolates (Martins et al, 1997;Monteil et al, 1997;Hunter et al, 1998). In addition, in this study, a few oral isolates showed cross-resistance to the azoles.…”
Section: Susceptibility Of C Albicans To Antifungal Agentssupporting
confidence: 92%
“…This may be due to the infrequent use of 5-fluorocytosine in dentistry. Varying susceptibility of the tested isolates to the azolegroup antifungal agents is in accordance with recent reports of oral yeast isolates (Martins et al, 1997;Monteil et al, 1997;Hunter et al, 1998). In addition, in this study, a few oral isolates showed cross-resistance to the azoles.…”
Section: Susceptibility Of C Albicans To Antifungal Agentssupporting
confidence: 92%
“…In one study, approximately onethird of late-stage AIDS patients carried drug-resistant C. albicans in their oral cavities (35). Fluconazole-resistant (FLC R ) C. albicans is now seen in both HIV and non-HIV patients who have never been exposed to fluconazole (38).…”
mentioning
confidence: 99%
“…Antifungal resistance to fluconazole (FCZ), itraconazole (ITZ), and ketoconazole (KTZ) has been described and particularly in the setting of oral candidiasis in HIV/AIDS patients (6,14,15,25,26). Cross-sectional surveys have indicated a prevalence of FCZ-resistant oral C. albicans isolates of 12 to 19% (20).…”
mentioning
confidence: 99%
“…Cross-sectional surveys have indicated a prevalence of FCZ-resistant oral C. albicans isolates of 12 to 19% (20). Before the use of HAART, Martins et al (14,15) found a prevalence of Candida spp. resistant to FCZ of 22% in North Americans with oral candidiasis and of 14% in asymptomatically colonized patients.…”
mentioning
confidence: 99%